L'Università degli Studi di Firenze 1924-2004 Atti della tavola rotonda di presentazione del volume. Firenze, 17 Dicembre 2004 - Rogari, Sandro (Firenze University Press, 2005)
The volume collects the texts of the interventions held on December 17, 2004 in the Aula Magna of the University of Florence during the presentation of two volumes of the work published by Olschki publishing house "L'Università degli Studi di Firenze 1924-2004" (The University of Florence 1924-2004). After the introduction by the Rector Magnificus Augusto Marinelli, the work was discussed by historians Gian Paolo Brizzi and Paolo Prodi of the University of Bologna, Romano Paolo Coppini of the University of Pisa, and by professors Francesco Gurrieri and Sandro Rogari. The appendix of the volume contains a summary of the events organised in occasion of the eighty years anniversary, preceded by the introduction by Rector Augusto Marinelli and the index of the volumes.